1995
DOI: 10.1111/j.1525-1446.1995.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Progress in Smoking Cessation

Abstract: This study examined the ability of two specific measures of stressors associated with smoking cessation to act as predictors of progress through the stages of smoking cessation as described by Prochaska and DiClemente (1983). Specifically, a 19-item scale measuring barriers to smoking cessation and a 14-item scale measuring smoking cessation self-efficacy were completed by 127 smokers and self-quitters at three time points over a six-month period. Subjects who made progress through the stages of smoking cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
(16 reference statements)
0
42
0
Order By: Relevance
“…The BCS also has evidenced good content and predictive validity (Macnee & Talsma, 1995a). To maintain consistency with past work using the BCS (e.g., Macnee & Talsma, 1995b), we used only the total BCS score in this study.…”
Section: Positive Affect Negative Affect Schedule (Panas)mentioning
confidence: 98%
“…The BCS also has evidenced good content and predictive validity (Macnee & Talsma, 1995a). To maintain consistency with past work using the BCS (e.g., Macnee & Talsma, 1995b), we used only the total BCS score in this study.…”
Section: Positive Affect Negative Affect Schedule (Panas)mentioning
confidence: 98%
“…The BCS also has evidenced good content and predictive validity (Macnee & Talsma, 1995a). To maintain consistency with past work using the BCS (e.g., Macnee & Talsma, 1995b;Zvolensky, Vujanovic et al, 2007), only the total BCS score was utilized in this study.…”
Section: The Structured Clinical Interview For Dsm-iv Axis I Disordermentioning
confidence: 99%
“…Ethnic minorities and those with medical or comorbid psychological disorders, who are often of low SES, are typically underrepresented in interventions. Recent research assessing barriers to entering smoking cessation treatment in underserved, low SES smokers has suggested that these smokers have distinct perceived barriers to cessation treatment, including little access to information about smoking cessation, lack of knowledge about the smoking-related health risks, cultural beliefs related to smoking, stigma attached to using cessation resources, disbelief in efficacy, psychological comorbidity, unreliable phone service, lack of childcare, transience, lack of transportation, time constraints, cost of treatment, lack of insurance, financial stress, lack of coping skills and low motivation and self-efficacy Hughes, Cohen, & Callas, 2009;Hutchinson et al, 2008;King, Borrelli, Black, Pinto, & Marcus, 1997;Lazev, Vidrine, & Arduino, 2004;Macnee & Talsma, 1995;Okuyemi et al, 2006;Roddy, Antoniak, Britton, Molyneux, & Lewis, 2006;Siahpush, Yong, Borland, Reid, & Hammond, 2009).…”
mentioning
confidence: 99%